Does Corporate Governance Affect Bank Performance? Empirical Evidence from India - Kumar, Naresh; Sudesh (Prabandhan: Indian Journal of Management, 2019)
The performance of corporates is a vital concept that relates to the paths and manners in which financial and non-financial resources available to a firm are shrewdly used to accomplish the overall objective of a firm. The comprehensive motive of good governance of corporates is amplification of investors’ confidence in the economy of a country. The aim of the present study was to assess the impact of corporate governance (practices) on performance of selected banks. Using a non-binary approach, unweighted index was constructed for the present study. Trichotomous approach was followed to quantify each sub-variable of corporate governance. All scheduled public sector banks, which were listed on BSE as well as NSE as on April 01, 2014 were selected. The study used secondary data, which were obtained from government publications, respective banks’ websites, corporate governance reports, and annual reports of selected banks. Prowess database, Capitaline Plus database, and Indian Boards database were also used to assemble the data. The data were put together for a period of 10 financial years from 2006-07 to 2015-16. The panel data were analyzed through STATA Software by using descriptive statistics and econometric models, that is, pooled ordinary least squares, fixed-effects, and random-effects models. Test for normality, test for multicollinearity, test for heteroskedasticity, test for serial correlation, Hausman test, and LM test were also carried out for the present study. The study found that corporate governance had a significant role in determining the basic earnings per share; whereas, corporate governance did not significantly influence the performance measure Tobins’Q.